Compound Kushen injection reduces severity of radiation-induced gastrointestinal mucositis in rats - Harata-Lee, Yuka; Qu, Zhipeng; Bateman, Emma; Xiao, Xi; Keller, Marianne D.; Bowen, Joanne; Wang, Wei; Adelson, David L. (Frontiers in Oncology, 2022)
Mucositis, or damage/injury to mucous membranes of the alimentary, respiratory, or genitourinary tract is the major side effect associated with anticancer radiotherapies. Because there is no effective treatment for mucositis at present, this is a particular issue as it limits the dose of therapy in cancer patients and significantly affects their quality of life. Gastrointestinal mucositis (GIM) occurs in patients receiving radiotherapies to treat cancers of the stomach, abdomen, and pelvis. It involves inflammation and ulceration of the gastrointestinal (GI) tract causing diarrhoea, nausea and vomiting, abdominal pain and bloating. However, there is currently no effective treatment for this debilitating condition. In this study, we investigated the potential of a type of traditional Chinese medicine (TCM), compound Kushen injection (CKI), as a treatment for GIM. It has previously been shown that major groups of chemical compounds found in CKI have anti-inflammatory effects and are capable of inhibiting the expression of pro-inflammatory cytokines. Intraperitoneal administration of CKI to Sprague Dawley (SD) rats that concurrentlyreceived abdominal irradiation over 5 fractions resulted in reduced severity of GIM symptoms compared to rats administered a vehicle control. Histological examination of the intestinal tissues revealed significantly less damaged villus epithelium in CKI administered rats that had reduced numbers of apoptotic cells in the crypts. Furthermore, it was also found that CKI treatment led to decreased levels of inflammatory factors including lower levels of interleukin (IL)-1β and IL-6 as well as myeloperoxidase (MPO) producing cells in the intestinal mucosa. Together, our data indicate a novel effect of CKI to reduce the symptoms of radiation induced GIM by inhibiting inflammation in the mucosa and apoptosis of epithelial cells.